Brucella-Induced Acute Psychosis: A Novel Cause of Acute Psychosis. (5th March 2021) - Obuaya, Chi-Chi; Gangatharan, Gayathri Thivyaa; Karra, Efthimia
Abstract : Background . Infections have long been linked to psychosis and categorised within "secondary" psychoses. To date, there have been few reports of psychosis linked to brucellosis. This case report aims to present one such case. Case Presentation . A 31-year-old man was admitted to a general hospital with pyrexia, severe right upper quadrant pain, and an acute psychosis following a two-week holiday in South East Asia and the Mediterranean. Serological tests revealed that he had brucellosis. Following antibiotic treatment, the psychotic symptoms abated and he was discharged within ten days of hospitalisation. Conclusions . This case of organic psychosis highlights the importance of considering brucellosis as a rare cause of acute psychosis. The exact mechanism of Brucella -induced psychosis remains unclear.